ANALISIS VEGETASI TUMBUHAN PANTAI PADA KAWASAN WISATA PASIR JAMBAK, KOTA PADANG - Annisa Novianti Samin; Chairul Chairul; Erizal Mukhtar (Biology Department, Mathematics and natural science, Tadulako University, 2016)
Research on the Analysis of Plant Vegetation on Coastal Tourism Regions Pasir Jambak, Padang City had been done starting from May till September 2015. The goal of this research is to find out the composition and the structure of coastal vegetation on Tourism Regions Pasir Jambak, Padang city. This research uses a plot squared method using belt transects and laying a plot carried out systematically sampling. The results shown at tree level found as many as 5 families, 5 species and 36 individuals. The next level of sapling found as many as 4 families, 4 species and 36 individuals, while at the level of seedling was found as many as 12 families, 19 species and 712 individuals. The highest important value at the level of the tree that Casuarina equisetifolia (214.72%) and the lowest was Pongamia sp. (8.22%). Furthermore, on the level of sapling which has the highest importance Cerbera manghas (156.6%) and the lowest was Glochidon sp. (16.2%), while the highest rate of seedling Spaghneticola trilobata (105.5%), the lowest was Ardisia littoralis, Lantana camara and Blumea chinensis with the value (1.8%). Diversity index is low both at tree level (0.33), the level of sapling (0.46) and the level of seedling (0.77).Keyword : Composition, Structure, Diversity, Plant on coastal